Diurnal variability of polycyclic aromatic compound (PAC) concentrations: Relationship with meteorological conditions and inferred sources. (December 2015) - Alam, Mohammed S.; Keyte, Ian J.; Yin, Jianxin; Stark, Christopher; Jones, Alan M.; Harrison, Roy M.
Abstract: Polycyclic aromatic hydrocarbons (PAH) and their nitro and oxy derivatives have been sampled every three hours over one week in winter at two sites in Birmingham UK. One site is heavily influenced by road traffic and is close to residential dwellings, while the other site is a background urban location at some distance from both sources of emission. The time series of concentrations has been examined along with the ratio of concentrations between the two sampling sites. A comparison of averaged diurnal profiles has shown different patterns of behaviour which has been investigated through calculating ratios of concentration at 18:00–21:00 h relative to that at 06:00–09:00 h. This allows identification of those compounds with a strong contribution to a traffic-related maximum at 06:00–09:00 h which are predominantly the low molecular weight PAHs, together with a substantial group of quinones and nitro-PAHs. Changes in partitioning between vapour and particulate forms are unlikely to influence the ratio as the mean temperature at both times was almost identical. Most compounds show an appreciable increase in concentrations in the evening which is attributed to residential heating emissions. Compounds dominated by this source show high ratios of 18:00–21:00 concentrations relative to 06:00–09:00 concentrations and include higher molecular weight PAH and a substantial group of both quinones and nitro-PAH. The behaviour of retene, normally taken as an indicator of biomass burning, is suggestive of wood smoke only being one contributor to the evening peak in PAH and their derivatives, with coal combustion presumably being the other main contributor. Variations of PAH concentrations with wind speed show a dilution behaviour consistent with other primary pollutants, and high concentrations of a range of air pollutants were observed in an episode of low temperatures and low wind speeds towards the end of the overall sampling period consistent with poor local dispersion processes. Results from a short summer campaign give indications of the formation of some nitro-PAH by atmospheric chemical reactions. Highlights: A wide range of PAH, oxy-PAH and nitro-PAH are analysed. Roadside and urban background are measured. Eight 3-h samples are collected each day. Diurnal profiles reveal compounds generated from traffic and domestic combustion. Isomer ratios show some influence of atmospheric chemistry.